Effects of Trace Metal Profiles Characteristic for Autism on Synapses in Cultured Neurons. (23rd February 2015) - Hagmeyer, Simone; Mangus, Katharina; Boeckers, Tobias M.; Grabrucker, Andreas M.
Abstract : Various recent studies revealed that biometal dyshomeostasis plays a crucial role in the pathogenesis of neurological disorders such as autism spectrum disorders (ASD). Substantial evidence indicates that disrupted neuronal homeostasis of different metal ions such as Fe, Cu, Pb, Hg, Se, and Zn may mediate synaptic dysfunction and impair synapse formation and maturation. Here, we performed in vitro studies investigating the consequences of an imbalance of transition metals on glutamatergic synapses of hippocampal neurons. We analyzed whether an imbalance of any one metal ion alters cell health and synapse numbers. Moreover, we evaluated whether a biometal profile characteristic for ASD patients influences synapse formation, maturation, and composition regarding NMDA receptor subunits and Shank proteins. Our results show that an ASD like biometal profile leads to a reduction of NMDAR (NR/Grin/GluN) subunit 1 and 2a, as well as Shank gene expression along with a reduction of synapse density. Additionally, synaptic protein levels of GluN2a and Shanks are reduced. Although Zn supplementation is able to rescue the aforementioned alterations, Zn deficiency is not solely responsible as causative factor. Thus, we conclude that balancing Zn levels in ASD might be a prime target to normalize synaptic alterations caused by biometal dyshomeostasis.